Molecular, immunological and neurophysiological evaluations for early diagnosis of neural impairment in seropositive leprosy household contacts. - Diogo Fernandes Dos Santos; Matheus Rocha Mendonça; Douglas Eulálio Antunes; Elaine Fávaro Pípi Sabino; Raquel Campos Pereira; Luiz Ricardo Goulart; Isabela Maria Bernardes Goulart (Public Library of Science (PLoS), 2018)
Household contacts constitute the highest risk group for leprosy development, and despite significant progress in the disease control, early diagnosis remains the primary goals for leprosy management programs.We have recruited 175 seropositive and 35 seronegative household contacts from 2014 to 2016, who were subjected to an extensive protocol that included clinical, molecular (peripheral blood qPCR, slit-skin smear qPCR, skin biopsy qPCR) and electroneuromyographic evaluations.The positivity of peripheral blood qPCR of seropositive contacts was 40.6% (71/175) whereas only 8.6% (3/35) were qPCR positive in seronegative contacts (p = 0.0003). For the slit-skin smear, only 4% (7/175) of seropositive contacts presented positive bacilloscopy, whereas the qPCR detected 47.4% (83/175) positivity in this group compared with only 17.1% (6/35) in seronegative contacts (p = 0.0009). In the ENMG evaluation of contacts, 31.4% (55/175) of seropositives presented some neural impairment, and 13.3% (4/35) in seronegatives (p = 0.0163). The presence of neural thickening conferred a 2.94-fold higher chance of ENMG abnormality (p = 0.0031). Seropositive contacts presented a 4.04-fold higher chance of neural impairment (p = 0.0206). The peripheral blood qPCR positivity presented odds 2.08-fold higher towards neural impairment (OR, 2.08; p = 0.028). Contrarily, the presence of at least one BCG vaccine scar demonstrated 2.44-fold greater protection against neural impairment (OR = 0.41; p = 0.044).ELISA anti-PGL-I is the most important test in determining the increased chance of neural impairment in asymptomatic leprosy household contacts. The combination of the two assays (ELISA anti-PGL-I and peripheral blood qPCR) and the presence of BCG scar may identify individuals with higher chances of developing leprosy neuropathy, corroborating with the early diagnosis and treatment.